THE PRICE OF FAITH IN ALGERIA:1THE NEXUS OF GENDER AND RELIGION BASED ON THE FORBIDDEN WOMEN NOVEL - Mohamad Laudza’i Wafa (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
Sultana Mudjahed had to deal with a series of events that concern her pride as a woman, her faith, her identity, her community, her government and her past. Everything is in the form of a dramatic fiction written by Malika Mokeddem in her work "The Forbidden Women". Equipped with the viewpoint of the second main character, Vincent Chauvet, a French professor of mathematics who received a kidney donation from an Algerian woman, Mokeddem attempted to build a storyline by explaining the condition of the Algerian mentality. The experience of Algerian society which was once colonized by France plus the nuances of the Arab-Islamic cultural community was displayed in conversations between the main actors.